Competition of Voiding and Kirkendall Shift during Compound Growth in Reactive Diffusion–Alternative Models - Zaporozhets, T.V.; Storozhuk, N.V.; Gusak, A.M. (Металлофизика и новейшие технологии, 2016)
The simultaneous growth of both the phase-layer thickness and the void sizes during the intermetallic-compound formation with different mobilities of components and with a narrow concentration-range of homogeneity is described. This is done with account of competition for extra vacancies between dislocation steps and interfaces (K-sinks leading to Kirkendall shift) and voids (F-sinks providing Frenkel voiding). Three alternative models for three alternative places of preferential voids’ formation are formulated and compared. Possibilities of control over Kirkendall shift versus Frenkel voiding competition are discussed.